Die Auswirkungen der Steuer- und Sozialreformen der Jahre 1999 - 2005 auf die automatischen Stabilisatoren Deutschlands - Johannes Kalusche (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
Tax and social reforms aiming at lowering the tax burden and cutting social benefits may boost effciency and output, and improve market adjustment to shocks. But they may also reduce the impact of automatic stabilizers and so cause a less cyclical smoothing. This is problematic in the Economic and Monetary Union given the loss of national monetary autonomy. In this paper we examine the impact of the tax and social reforms of 1999-2005 in Germany on the automatic stabilizers. It is shown that the automatic stabilization power of several components of the public budget was changed by tax and social reforms. Nevertheless, it can be demonstrated that the automatic stabilization power of the public budget as a whole was not changed significantly.
Keywords: E62; H6; 330; Automatic Stabilizers; Business Cycles; Public Budget